MULTIDIMENSIONALITAS PERILAKU KEAGAMAAN: ANALISIS PARTISIPASI JEMAAT DALAM PERSEMBAHAN SYUKUR PANEN DI DESA BAKALINGA - Wendi Mbalengan; Purnama Pasande; Junni Yokiman (L-SAPIKA INDONESIA, 2026)
This study aims to analyze the effect of theological understanding, church and community influence, and economic conditions on congregation participation in the harvest thanksgiving offerings in Bakalinga Village, Banggai Kepulauan Regency, Central Sulawesi Province. This village was selected because it has a unique tradition in harvest offering practices that are maintained as part of the Christian community's life. The research utilizes a quantitative approach with an associative design, involving 100 congregation members as respondents selected through purposive sampling. Data were collected using a Likert scale-based questionnaire and analyzed through multiple linear regression with robust standard errors to address the violations of classical assumptions. The results showed that partially, the variables of theological understanding, church and community influence, and economic conditions do not have a significant independent effect on congregation participation. Nevertheless, simultaneous testing proves that these three factors jointly exert a significant influence. These findings confirm that congregation participation is a multidimensional phenomenon arising from the interaction between theological understanding, community social norms, economic conditions, and local cultural traditions. This study emphasizes the importance of a holistic approach in understanding religious behavior and provides practical implications for church pastoral strategies that are relevant to the local community context.